A study on safety climate at construction site Gerbang Nusajaya Sdn Bhd / Nurul Etylia Jefli and Nurul Asmida Hailudin - Jefli, Nurul Etylia; Hailudin, Nurul Asmida (Faculty of Business and Management, 2016)
The enormous growth in construction work done has highlighted safety climate as it becomes a pivotal issue since it been increasing at an alarming rate in the rate of occupational accidents. The emphasis of this study is to find factors that have an impact towards safety climate in the construction sites. Therefore, to investigate this phenomenon, the study is conducted to examine the relationship between communication, safety rules and procedure and also commitment towards safety climate. The study that has been conducted was using quantitative study and while the research instrument that being used is self-administered questions. Besides that, simple random sampling has been used as the sampling method for this study. The total number of respondents for this study is 70 persons. The researcher managed get fully back answered of 70 questionnaires. As for the response rate, all the respondent had answered the question which means 100% respond rate. Besides that, this study has been used Statistical Package for the Social Science (SPSS) version 23, to analyse all the data analysis and findings. Pearson correlation is being used to analysis if there is relationship between the independent variable and dependent variable while regression analysis is being used to measure which is the most influential factors among the variables. It is found that commitment factors are the most dominant effect towards safety climate.